When Task Constraints Delimit Movement Strategy: Implications for Isolated Joint Training in Dancers - Paige E. Rice; Paige E. Rice; Sophia Nimphius; Sophia Nimphius (Frontiers Media S.A., 2020)
Athletic performance is determined by numerous variables that cannot always be controlled or modified. Due to aesthetic requirements during sports such as dance, body alignment constrains possible movement solutions. Increased power transference around the ankle-joint, coupled with lower hip-joint power, has become a preferential strategy in dancers during leaps and may be considered a dance-specific stretch-shortening cycle (SSC) demand. Newell's theoretical model of interacting constraints includes organismic (or individual), environmental, and task constraints describing the different endogenous and exogenous constraints individuals must overcome for movement and athletic performance. The unique task constraints imposed during dance will be used as a model to justify an isolated joint, single-targeted block progression training to improve physical capacity within the context of motor behavior to enhance dance-specific SSC performance. The suggested ankle-specific block progression consists of isometrics, dynamic constant external resistance, accentuated eccentrics, and plyometrics. Such programming tactics intend to collectively induce tendon remodeling, muscle hypertrophy, greater maximal strength, improved rate of force development, increased motor unit firing rates, and enhanced dynamic movement performance. The current perspective provides a dualistic approach and justification (physiological and motor behavioral) for specific strength and conditioning programming strategies. We propose implementation of a single-targeted block progression program, inspired by Newell's theoretical model of interacting constraints, may elicit positive training adaptations in a directed manner in this population. The application of Newell's theoretical model in the context of a strength and conditioning supports development of musculoskeletal properties and control and is conceptually applicable to a range of athletes.